The Influence of Brand Ambassador Yuki Kato on the Purchase Decision of Senka Perfect Whip - Santi Delliana; Atika Gustiana Fitri (Ultimacomm: Jurnal Ilmu Komunikasi, 2022)
A brand ambassador is an effort made by a company to convey or promote its product brand through a celebrity as someone who promotes product advertisements to present the best image of a product with the aim that the advertised brand is immediately accepted by consumers and invites consumers to want to use the product. This study aims to determine the effect of Yuki Kato's brand ambassador on the purchasing decision of Senka Perfect Whip. This study uses stimulus-response theory and quantitative methods by distributing questionnaires to 400 respondents to followers of the @yukikt Instagram account. This study indicates the influence of brand ambassadors from four indicators, namely visibility, credibility, attractiveness, and strength. In addition, purchasing decisions consist of two indicators: attitude change and behavior change.